The Effect Of Leadership Style And Work Discipline Onemployee Performance At Lebong District Inspectorate - Lastri, Zelli; Soleh, Ahmad; Rahman, Abdul (Journal of Management, Economic, and Accounting, 2024)
This study aims to determine the effect of leadership style and work discipline on employeeperformance at the Lebong Regency Inspectorate. The sample in this study were 37 employees at the Lebong Regency Inspectorate. The sampling method is by means of a census. Data collection techniques by means of a questionnaire. The analytical method used is multiple regression analysis, hypothesis testing t and hypothesis testing f. The results of the regression equation are Y = 0.782 + 0.370X1 + 0.630X2, meaning that leadership style and work discipline have a positive influence on employee performance at the Lebong Regency Inspectorate. This illustrates that if the variables of leadership style and work discipline increase, employee performance will also increase. The result of the determination test is 0,591 or (59,1%). This shows that leadership style and work discipline affect employee performance at the Lebong Regency Inspectorate by 59.1%, while the rest (100 - 59.1% = 40.9%) are explained or influenced by other variables not examined. Leadership style and work discipline together have an influence on the performance of the Lebong Regency Inspectorate employees with a significant value of 0.000, less than 0.05. This illustrates that with an increase in leadership style and work discipline in employees, the performance of employees at the Lebong Regency Inspectorate will also increase. Leadership style has a positive and significant effect on employee performance at the Lebong Regency Inspectorate, because the significant value of 0.019 is smaller than 0.05. Work discipline has a positive and significant effect on employee performance at the Lebong Regency Inspectorate, with a significant value of 0.001 which is smaller than 0.05.